Performance and Competitiveness of Private Universities in Bengkulu Province - Arifah Hidayati, (Technium Social Sciences Journal, 2020)
The purpose of this study is to analyze the relationship between variables of market orientation, innovation orientation, and organizational learning orientation to the performance and competitiveness of private universities in Bengkulu province. The population of this study is the leaders of private universities, deans, and heads of study programs from 17 accredited Private Universities with a sample of 127 respondents. This research was conducted using a quantitative approach with survey methods. The design of this study is descriptive and verification research to analyze the causality between the studied variables. Data processing used descriptive analysis techniques and hypothesis testing with the Structural Equation Model (SEM). The results showed that market orientation, innovation orientation, and learning orientation had a significant effect on the performance and competitiveness of private universities. To increase the performance and competitiveness, leaders must be able to create an appropriate market orientation model and focus on service quality by considering the internal conditions of private universities. Policymakers should also make improvements or develop their learning orientation through education and training, and develop themselves in the fields of knowledge and technology. This is done as a material evaluation for development or innovation related to the revitalization of private universities to have the ability to adjust the progress of the age (future proof).